Emplacement and dewatering of the world's largest exposed sand injectite complex - Timothy J. Sherry; Christie D. Rowe; James D. Kirkpatrick; Emily E. Brodsky (Geochemistry, Geophysics, Geosystems)
Sandstone injectites form by up or down‐section flow of a mobilized sand slurry through fractures in overlying rock. They act as reservoirs and high‐permeability conduits through lower permeability rock in hydrocarbon systems. The Yellow Bank Creek Complex, Santa Cruz County, California is the largest known exposure of a sandstone injectite in the world. The complex contains granular textures that record processes of sand slurry flow, multiple pore fluids, and dewatering after emplacement. The injection was initially mobilized from a source containing both water and hydrocarbons. The water‐sand slurry reached emplacement depth first, due to lower fluid viscosity. As the sand slurry emplaced, the transition from slurry flow to pore water percolation occurred. This transition resulted in preferred flow channels ∼6 mm wide in which sand grains were weakly aligned (laminae). The hydrocarbon‐sand slurry intruded the dewatering sands and locally deformed the laminae. Compaction of the injectite deposit and pore fluid escape caused spaced compaction bands and dewatering pipes which created convolutions of the laminae. The hydrocarbon‐rich sand slurry is preserved today as dolomite‐cemented sand with oil inclusions. The laminae in this injectite are easily detected due to preferential iron oxide‐cementation of the well‐aligned sand laminae, and lack of cement in the alternating laminae. Subtle textures like these may develop during sand flow and be present but difficult to detect in other settings. They may explain permeability anisotropy in other sand deposits.